2022
DOI: 10.1155/2022/8402568
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Necroptosis-Related Prognostic Model in Head and Neck Squamous Cell Carcinoma

Abstract: Necroptosis is a new regulated cell-death mechanism that plays a critical role in various cancers. However, few studies have considered necroptosis-related genes (NRGs) as prognostic indexes for cancer. As one of the most common cancers in the world, head and neck squamous cell carcinoma (HNSCC) lacks effective diagnostic strategies at present. Hence, a series of novel prognostic indexes are required to support clinical diagnosis. Recently, many studies have confirmed that necroptosis was a key regulated mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Ultimately, a LASSO linear regression method was employed to screen and select 16 prognostic marker genes, which were utilized to construct a prognostic model. Furthermore, the clinical and expression data for GSE65858 and GSE41613 were obtained from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ) to serve as the validation set for the risk model 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, a LASSO linear regression method was employed to screen and select 16 prognostic marker genes, which were utilized to construct a prognostic model. Furthermore, the clinical and expression data for GSE65858 and GSE41613 were obtained from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ) to serve as the validation set for the risk model 8 .…”
Section: Methodsmentioning
confidence: 99%
“…We identified 651 genes associated with necrotizing apoptosis via GeneCards. A published study proposed 159 genes (Zhang et al, 2022). After removing the duplicated genes involved in the above GO terms, we had a total of 749 NRGs for the downstream analysis.…”
Section: Introductionmentioning
confidence: 99%
“…About 50% of necrosis in HNSCC is caused by necroptosis and suggested that necroptosis can release damage-associated molecular patterns (DAMPs) to promote cancer metastasis and cancer progression (11). The necroptosis-related prognostic risk model established by Zhang Z et al for HNSCC included 7 necroptosis-related genes (NRGs) that were significantly associated with the prognosis of HNSCC (12). However, after extracting the expression levels of 7 NRGs from the RNA-seq of HNSCC patients in the TCGA database, we found that there was no significant difference in the expression levels of VDAC1 and CHMP3 between HNSCC tissues and normal tissues, and the expression level of TRAF5 was relatively low.…”
Section: Introductionmentioning
confidence: 99%